2018
DOI: 10.1093/ndt/gfy376
|View full text |Cite
|
Sign up to set email alerts
|

Intradialytic exercise preconditioning: an exploratory study on the effect on myocardial stunning

Abstract: Background Exercise preconditioning provides immediate protection against cardiac ischemia in clinical/preclinical studies in subjects without chronic kidney disease. In individuals requiring renal replacement therapy, hemodialysis (HD) results in significant circulatory stress, causing acute ischemia with resultant recurrent and cumulative cardiac injury (myocardial stunning). Intradialytic exercise (IDE) has been utilized to improve functional status in individuals receiving HD. The objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
26
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 21 publications
5
26
1
Order By: Relevance
“…We intentionally chose to supplement intra-dialytic cycling with pre-dialysis functional training to verify this strategy as a possible improvement in content and volume of contemporary well-established intradialytic cycling programs. An additional argument for the retention of cycling in the experimental group is its putative effects in the prevention of HD related myocardial stunning 18 . In the extension phase of this trial, we sought to determine the achievable level of transfer of mastered functional exercise routines to a home environment on non-dialysis days in order to evaluate the sustainability of this approach.…”
mentioning
confidence: 99%
“…We intentionally chose to supplement intra-dialytic cycling with pre-dialysis functional training to verify this strategy as a possible improvement in content and volume of contemporary well-established intradialytic cycling programs. An additional argument for the retention of cycling in the experimental group is its putative effects in the prevention of HD related myocardial stunning 18 . In the extension phase of this trial, we sought to determine the achievable level of transfer of mastered functional exercise routines to a home environment on non-dialysis days in order to evaluate the sustainability of this approach.…”
mentioning
confidence: 99%
“…From this, SBP (Table 2) was similar in the control session (132.60 mm Hg ± 5.13) to the exercise session (136.76 mm Hg ± 6.44). Recent studies examining blood pressure in subjects receiving intradialytic exercise reported similar findings with no differences in either control or exercise sessions (21,22). Other researchers observed no changes in SBP between control (140.90 mm Hg ± 22.30) and exercise sessions (131.30 mm Hg ± 20.00) (21).…”
Section: Discussionmentioning
confidence: 79%
“…Recent studies examining blood pressure in subjects receiving intradialytic exercise reported similar findings with no differences in either control or exercise sessions (21,22). Other researchers observed no changes in SBP between control (140.90 mm Hg ± 22.30) and exercise sessions (131.30 mm Hg ± 20.00) (21). However, other researchers have demonstrated significant increases in SBP with the introduction of intradialytic exercise (6,9,23).…”
Section: Discussionmentioning
confidence: 85%
“…Exercise during hemodialysis may also improve solute removal and stabilize cardiovascular hemodynamics (12). Exploratory studies of intradialytic cycle ergometry have recently reported improved O 2 saturation, partial pressure of O 2 (Pa O2 ), and reduced myocardial regional wall motion abnormalities, indicative of attenuated cardiac stunning (13)(14)(15). As such, this form of exercise may help to reduce the side effects and risks associated with hemodialysis.…”
Section: Introductionmentioning
confidence: 99%